DETERMINAN PERILAKU MAKAN MIE INSTAN PADA SISWA SMAN 4 KOTA BOGOR DI MASA PANDEMI COVID-19 - Natia Defiana (2021)
Pandemic covid-19 affects people's diet, especially in adolescents who are very vulnerable to bad eating habits. In addition, instant noodles are one of the foods consumed by the community during the pandemic because it lasts a long period of time, easy to serve and at any time can be cooked. This study aims to find out the factors that influence instant noodle eating behavior in students of SMAN 4 Bogor during the covid-19 pandemic. This study uses cross-sectional design, research respondents numbered 100 active students at SMAN 4 Bogor and met the criteria of research inclusion. The data was taken by filling out an online questionnaire. Data analysis was conducted with Chi Square test (bivariate analysis) and Multiple Logistics Regression (multivariate analysis). Based on the results of statistical tests there is no relationship between the behavior of reading food labels (p=0.081) and there is a relationship between the behavior of choosing instant noodles (p=0.007), the availability of instant noodles (p=0.006), nutritional knowledge (p=0.033) and family income (p=0.007) to the instant noodle eating behavior of students. Based on the results of multivariate statistical tests, family income (OR=5,734) is the most influential factor in students' instant noodle eating behavior. So it can be concluded that family income is the most influencing factor in the behavior of eating instant noodles SMAN 4 Bogor during the covid-19 pandemic.